2016
DOI: 10.1007/s12298-016-0382-y
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic stress affects the expression profile of genes of 14-3-3 proteins in the shoot of mycorrhiza colonized rice

Abstract: The intimate association between the arbuscular mycorrhizal fungi and host plants helps the latter in phosphate acquisition in exchange of carbohydrates and in enhanced stress tolerance. Similarly, the ubiquitous 14-3-3 protein family is known to be a major regulator of plant metabolism and stress responses. However, the involvement of mycorrhiza and plant 14-3-3 proteins interaction in plant response to environmental stimuli, such as arsenic (As) stress, is yet unknown. In this study, we analysed the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In higher plants, 14-3-3 proteins always bind to the signaling molecules and play crucial roles in stress responses and signal transduction [40]. In rice, the genes encoding the 14-3-3 protein was obviously up-regulated by arsenic stress [41]. In aluminum (Al)-tolerant soybean roots, the expression of 14-3-3 proteins were significantly enhanced by Al stress [42].…”
Section: Stress Induced Oxidative Injuries and Inhibited Photosyntmentioning
confidence: 99%
“…In higher plants, 14-3-3 proteins always bind to the signaling molecules and play crucial roles in stress responses and signal transduction [40]. In rice, the genes encoding the 14-3-3 protein was obviously up-regulated by arsenic stress [41]. In aluminum (Al)-tolerant soybean roots, the expression of 14-3-3 proteins were significantly enhanced by Al stress [42].…”
Section: Stress Induced Oxidative Injuries and Inhibited Photosyntmentioning
confidence: 99%
“…This indicated that F1 seeds or seedling roots also excreted As from inside the seeds or seedlings containing relatively high As. However, with high concentrations of As in the growth media, As can also enter the seedlings, displacing phosphate and silicates in biological reactions, inhibiting metabolic processes, and mediating gene expression (Carbonell et al 1998;Summers 2009;Pathare et al 2016).…”
Section: Mechanisms Of Intergenerational Effectsmentioning
confidence: 99%
“…The 14-3-3 proteins can also affect phosphate uptake and transport processes in the plants. A recent study on rice plants inoculated with AM fungi (R. irregularis) showed an upregulation of 14-3-3 genes under AMF colonization (Pathare et al, 2016) indicating their possible involvement in AMF-mediated As toxicity amelioration in rice plants. Chan et al (2013) tested a combination approach utilizing three Glomus species (G. geosporum, G. mosseae, G. versiforme) for modulating As stress in rice.…”
Section: Ranjan Et Al 2018mentioning
confidence: 95%